Analysis of village fund management in poverty alleviation at Pasaman Regency, West Sumatra - Ferta Daforsa; Hefrizal Handra (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This research examines the effect of village fund management toward poverty alleviation in Pasaman Regency, West Sumatra. The data of the research were obtained from the Social Service and Regional Government of Pasaman Regency in 2016-2018. The sample of this research is 37 villages at Pasaman regency in 12 sub-districts. The research was conducted using the panel data regression method. The results showed that each policy area of village fund use in Pasaman Regency was able to reduce poverty simultaneously. Partially from the four research variables, it was found that community development and infrastructure development policies were able to inﬂuence the reduction of poverty in Pasaman Regency